Identification of Geothermal Distribution in The Banyu Biru Hot Water Source using The Magnetic Method - Ahmad Luthfin; Nur Amilatu Jubaidah (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
The geothermal phenomenon in Banyu Biru hot springs in Gondangwetan Village, Jatikalen District, Nganjuk Regency, has the potential to be developed into a tourist spot and an alternative renewable energy source that is environmentally friendly; for example, a geothermal power plant. So it is necessary to know the distribution of geothermal reservoirs and how much potential energy is contained. This research aims to determine the distribution of geothermal energy in the research area and its geological structure. This study used the Magnetic Method for secondary data obtained from NOAA satellite data. Data acquisition with an area of 2000 meters x 2000 meters obtained 100 data with a spacing of 200 meters. Based on research results, geothermal bursts have a low anomaly value of -50 nT to 25 nT. The low anomaly distribution can be used to determine the geothermal distribution in the area, assuming that areas with the same anomaly value indicate the presence of geothermal energy. The geology of the study area has five layers, namely: Topsoil (soil) has a susceptibility value of 0.0000377 SI, Alluvium has a susceptibility value of 0.00144513 SI, Tufan Clay has a susceptibility value of 0.00692407 SI, Limestone Tuff has a susceptibility value of 0.125713399 SI and Breccia (Andesite and Basalt) has a susceptibility value 0.0126292 SI. The depth of the geothermal source in the study area is ± 250 meters below the surface.